Climate teleconnections influence on West Africa's terrestrial water storage. Issue 18 (21st July 2017) - Ndehedehe, Christopher E.; Awange, Joseph L.; Kuhn, Michael; Agutu, Nathan O.; Fukuda, Yoichi
Abstract: There is some evidence of rapid changes in the global atmosphere and hydrological cycle caused by the influence of climate variability. In West Africa, such changes impact directly on water resources leading to incessant extreme hydro‐meteorological conditions. This study examines the association of three global climate teleconnections—El‐Niño Southern Oscillation (ENSO), Indian Ocean Dipole (IOD), and Atlantic Multi‐decadal Oscillation (AMO) with changes in terrestrial water storage (TWS) derived from both Modern‐Era Retrospective Analysis for Research and Applications (MERRA, 1980–2015) and Gravity Recovery and Climate Experiment (GRACE, 2002–2014). In the Sahel region, positive phase of AMO coincided with above‐normal rainfall (wet conditions) and the negative phase with drought conditions and confirms the observed statistically significant association ( r = 0.62) between AMO and the temporal evolutions of standardised precipitation index. This relationship corroborates the observed presence of AMO‐driven TWS in much of the Sahel region (though considerably weak in some areas). Although ENSO appears to be more associated with GRACE‐derived TWS over the Volta basin ( r =−0.40), this study also shows a strong presence of AMO‐ and ENSO‐induced TWS derived from MERRA reanalysis data in the coastal West African countries and most of the regions below latitude 10°N. The observed presence of ENSO‐ and AMO‐driven TWS is noticeable in tropical areas with relatively high annual/bimodal rainfall and strong inter‐annual variations in surface water. The AMO has a wider footprint and sphere of influence on the region's TWS and suggests the important role of North Atlantic Ocean. IOD‐related TWS also exists in West Africa and its influence on the region's hydrology maybe secondary and somewhat complementary. Nonetheless, presumptive evidence from the study indicates that ENSO and AMO are the two major climatic indices more likely to impact on West Africa's TWS.